2014
DOI: 10.1016/j.bbabio.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of putative protomer crosstalk in the trimeric transporter BetP: The heterotrimer approach

Abstract: The homotrimeric, secondary active betaine carrier BetP from Corynebacterium glutamicum is a model system for stress-regulated transport in bacteria. Its activity responds to hyperosmotic stress and it harbors two different functions, transport catalysis (betaine uptake) and stimulus sensing, resp. activity regulation. Structural information from 2D and 3D crystals as well as functional analysis of monomerized BetP suggested the presence of conformational crosstalk between the individual protomers. To study wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…We do know that each transporter is an oligomer (ProP and OpuA are dimers; BetP is a trimer; Wood, 2011b ). The role of oligomerization in osmosensing by BetP has been explored experimentally but remains uncertain ( Becker et al, 2014 ). The roles of oligomerization for ProP and OpuA remain unknown.…”
Section: Proteoliposome-based Analysis Of Osmosensing By Prop Betp mentioning
confidence: 99%
“…We do know that each transporter is an oligomer (ProP and OpuA are dimers; BetP is a trimer; Wood, 2011b ). The role of oligomerization in osmosensing by BetP has been explored experimentally but remains uncertain ( Becker et al, 2014 ). The roles of oligomerization for ProP and OpuA remain unknown.…”
Section: Proteoliposome-based Analysis Of Osmosensing By Prop Betp mentioning
confidence: 99%
“…Furthermore, analysis of monomeric BetP revealed that the transporter is no longer regulated by osmotic stress, but retains its ability to transport betaine 18 . However, a heterotrimer approach provides evidence for the absence of functionally significant conformational crosstalk between the protomers of BetP on the level of both transport and regulation 19 . Nonetheless, the difference between the activities of monomeric BetP (13% of the V max of the trimer) and the orphan protomer in the heterotrimer (full activity) suggests that optimal activity requires physical contacts between the protomers 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…BetP occurs also as a homotrimer 16,17 . Investigation of the role of trimerization in BetP revealed that the trimer is not essential for the ability to accumulate betaine 18,19 . However, BetP loses its function as a regulator when in an engineered monomeric state probably due to altered protein interactions of the extended N- and/or C-terminal domains performing this regulation 18 .…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few examples where multimeric membrane proteins encoded in a single polypeptide have been purified for functional and spectroscopic studies ( Raghuraman et al, 2012 ; Lim et al, 2016 ; Last et al, 2016 ; Wang et al, 2016 ). In the co-expression approach, the wild type and the mutant subunits are co-expressed in the same cell ( Becker et al, 2014 ; Lu et al, 2017 ), wherein the random mixing of the subunits during assembly results in the generation of heteromeric and homomeric proteins. Placing different purification tags on the wild type and the mutant subunits allows the purification of the desired heteromeric protein.…”
Section: Introductionmentioning
confidence: 99%